DILEMA DAN PROBLEMA PEMBELAJARAN DARING - Thesalonika, Nathasya; Herlambang, Yusuf Tri (Jurnal Dinamika Pendidikan, 2021)
This research was conducted with the aim of describing the dilemmas and problems in the implementation of online learning. In this increasingly technological and sophisticated era, technology is very useful in its use in all aspects of life. The use of this technology also has an important role in the educational aspect. The existence of the Covid-19 pandemic period made the learning implementation system changed into virtual face-to-face learning or online learning which was originally carried out face-to-face between students and teachers at school. Like it or not, students must understand and have the ability to use technology to optimally follow this online learning system. In the implementation of this online learning there are various problems that occur and are faced by educators, students, and parents in various matters such as readiness in implementation, facilities, and various other things. This research uses literature study method. This method is done by finding and collecting various data and information about the research discussed by searching from various sources such as books, journals, and other media that can be accessed and relevant to the research discussion. In this research, it can show how the implementation of online learning, the problems that occur in the implementation of online learning, and the problems faced by students, teachers, and parents in the process of implementing online learning.